The social movement of street vendors to maintain their business places in Bandung - Rina Hermawati; Oekan S. Abdoellah; Budhi Gunawan; Selly Riawanti (Faculty of Social and Political Science, Universitas Airlangga, 2019)
This study views street vendors as public issues which are related to the conflict over public spaces between the government and the street vendors. The conflict was derived from differences in the interpretation and meaning of public spaces. The government has visions of order in the city and tries to control the street vendor in public place. However, the street vendors interpret public place as a strategic place to conduct their business and try to defend their existence in it. The differences in interpretation encouraged the birth of street vendor movement in Bandung. This research employed social movement concept to describes how street vendors try to construct their identities, build up the strength of their organization/association, frame and disseminate issues, and establish some coalitions. It used a qualitative method with case study research by attaining some cases of street vendors in Bandung and observing their news through newspaper and online media between 2015-2016, as well as conducting some interviews with key informants. The data collected through participative observation, thorough interview with street vendors, municipal government, street vendors’ organizations/associations, and focus group discussion. This research showed that the process of identity construction is carried out informally through kinship system. Furthermore, the street vendors built their movement based on issues of unjust policy which is supported by right to seek livelihood, marginalization issue, and limited access to formal economic sectors. These issues become their justification to maintain their business in public places and their efforts to go against government interpretation of public places which become their foundation to formulate policies about street vendors. Lastly, to strengthen their bargaining position against the government, they establish three types of coalition; political coalition, political-economy coalition, and economy coalition.